PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTU MIND MAPPING PADA PEMBELAJARAN IPS SISWA KELAS V SD NEGERI 15 LUBUKLINGGAU - Cahya Madrani; Ahmad Gawdy Prananosa; Andri Valen (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to determine the completeness of student learning outcomes after the Application of the Mind Mapping Assisted Problem Based Learning Model in Social Studies Learning for Class V SD Negeri 15 Lubuklinggau Significant Complete. This type of research is quantitative research and the research method used is quasi-experiment using pre-test and post-test research designs. Using multiple choice questions of 16 questions. The research sample was VB class consisting of 23 students and data analysis techniques with the following steps: Normality Test, T-Test. Based on the results of the T-Test analysis, the value of tcount (1.75) and ttable (1.73) when compared means tcount > ttable, after applying Problem Based Learning Assisted Mind Mapping it is significantly complete with a significant level of 0.05 so it can be concluded that the results studying social studies for fifth grade students at SD Negeri 15 Lubuklinggau after applying the Mind Mapping Assisted Problem Based Learning Model significantly completed. Keywords: Application, Learning Outcomes, Problem Based Learning, Mind Mapping